Mexico : Selected Issues. (IMF Staff Country Reports; Country Report, 2004)
This Selected Issues paper analyzes the sources of Mexico's economic growth since the 1960s, and compares various decompositions of historical growth into trend and cyclical components. The role of the implied output gaps in the inflation process is assessed. The paper presents medium-term paths for GDP based on alternative productivity growth rates. The paper also describes the significant steps Mexico has taken to strengthen the structure of its public debt in recent years, both in terms of currency composition and maturity.